Galeria Foksal 1966-1988. - Borowski, Wieslaw; Galeria Foksal, Warszawa (Warszawa : Galeria Foksal, 1989)
Kantor, Tadeusz ; Krasinski, Edward ; Englund, Lars ; Druga Grupa ; Stazewski, Henryk ; Gostomski, Zbigniew ; Jacquet, Alain ; Vautier, Ben ; Barry, Robert ; Wodiczko, Krzysztof ; Anselmo, Giovanni ; Targowski, Zygmunt ; Marioni, Tom ; Boltanski, Christian ; Messager, Annette ; etc.
Engels
boek